Analysis of Factors Associated with Patient Satisfaction in the Outpatient Unit - Besty Sibarani; Didik Dwi Sanyoto; Bahrul Ilmi; Endah Labati Silapurna; Zairin Noor (Journal La Medihealtico, 2026)
The patient satisfaction level at the Outpatient Unit of the Sengayam Regional General Hospital (RSUD) in the second quarter of 2025 was recorded at 84.23, which means it is still below the minimum service standard of ≥95%. This study aims to analyze factors associated with patient satisfaction through a literature review using a qualitative descriptive approach on scientific articles published between 2015 and 2025. The analysis results indicate that the reliability dimension is the most critical factor as it is directly related to the consistency of staff in accurately following standard operating procedures. In addition to clinical aspects, cost factors such as tariff transparency and physical facilities including the comfort of waiting areas and cleanliness were found to be significant in shaping patients’ perceived value. This satisfaction dynamic is not static but continues to evolve alongside patients’ demographic characteristics and the ease of accessing digital information, which makes the public’s expectations regarding healthcare services increasingly critical and personalized. In conclusion, effective coordination across the SERVQUAL dimensions, particularly regarding reliability and tangible evidence, serves as the primary strategy for Sengayam General Hospital to enhance service quality and achieve the established satisfaction standards.